KONTRIBUSI KH. TUBAGUS AHMAD HASURI THOHIR DALAM MENGEMBANGKAN PENDIDIKAN ISLAM DI KOTA SERANG MELALUI PONDOK PESANTREN AT-THOHIRIYYAH: KONTRIBUSI KH. TUBAGUS AHMAD HASURI THOHIR DALAM MENGEMBANGKAN PENDIDIKAN ISLAM DI KOTA SERANG MELALUI PONDOK PESANTREN AT-THOHIRIYYAH - Ahmad Munada, TB; Sirojudin, Rumbang; Hadiyyin, Ikhwan; Wasehudin, Wasehudin (ISLAMIKA, 2024)
This research unveils the significant role played by KH. TB. Ahmad Hasuri Thohir in advancing Islamic education through the establishment of an Islamic boarding school named At-Thohiriyyah. This boarding school stands out as a noteworthy Islamic educational institution in the city of Serang. Employing a qualitative method with a historical approach, the research utilizes interview and observation techniques to gather data. The findings of the study highlight KH. TB. Ahmad Hasuri Thohir's contribution through At-Thohiriyyah, which focuses on providing Islamic educational opportunities in Serang, aiming to nurture students with strong morals, expansive knowledge, and proficiency in understanding classical Islamic texts. Many graduates from At-Thohiriyyah have gone on to engage in academia, become successors to scholars, establish their own Islamic boarding schools, and contribute to the development of Islamic knowledge through scholarly works. In conclusion, the research underscores that KH. TB. Hasuri Thohir's efforts to develop Islamic education, manifested through the establishment of At-Thohiriyyah, have successfully positioned it as a favored Islamic educational institution in the community, evident in the achievements of students mastering religious knowledge and making scholarly contributions.